2013
DOI: 10.1192/bjp.bp.113.129486
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal depression symptoms and nutrition, and child cognitive function

Abstract: Prenatal interventions aimed at the well-being of children of parents with depression should consider targeting the nutritional environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 27 publications
12
111
3
1
Order By: Relevance
“…Barker and colleagues found prenatal depressive symptoms were negatively associated with cognitive function in 8-year old offspring, which was partially mediated through prenatal nutrition. These results were robust to postnatal depression and nutrition, although were modest in effect size (Barker et al, 2013). Santucci and colleagues did not find evidence of an association between un-medicated prenatal depressive disorder (diagnosed with the Structured Clinical Interview for DSM-IV ) and the MDI or PDI scales of the BSID-II at any point between 12 and 78 months postnatally (Santucci et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Barker and colleagues found prenatal depressive symptoms were negatively associated with cognitive function in 8-year old offspring, which was partially mediated through prenatal nutrition. These results were robust to postnatal depression and nutrition, although were modest in effect size (Barker et al, 2013). Santucci and colleagues did not find evidence of an association between un-medicated prenatal depressive disorder (diagnosed with the Structured Clinical Interview for DSM-IV ) and the MDI or PDI scales of the BSID-II at any point between 12 and 78 months postnatally (Santucci et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Primarily, this research has focused specifically on the effects of medication treatment for depression in pregnancy (most commonly with SSRIs) (Hanley et al, 2013). Research that has attempted to estimate the functional neurodevelopmental effects of prenatal maternal depression independent of medication to treat depression is scarce and has resulted in inconsistent, primarily null findings (Barker et al, 2013; Nulman et al, 2015, 2012; Santucci et al, 2014). However, research examining brain structure in preschoolers found women's second trimester depression scores negatively correlated with children's cortical thickness in right inferior frontal and middle temporal regions, which has been associated with negative neurodevelopmental outcomes (Lebel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with prior studies [25] . Maternal depression during pregnancy has been suggested to influence the developing fetus by altering the intra-uterine environment and interfering with neurodevelopmental processes, which could result in atypical cognitive and behavioral development [26] . However, this association could also be due to shared predictors of prenatal maternal depression and child development, such as socioeconomic disadvantage [27,28] or unhealthy behaviors (smoking, alcohol use).…”
Section: Patterns Of Association Between Maternal Depression and Chilmentioning
confidence: 99%
“…However, a literature review performed in the PubMed and SciELO databases, using the keywords food intake, pregnancy, mental health, and variations of dietary patterns and food patterns, retrieved only a few studies that evaluated the relationship between dietary patterns and mental health within the context of pregnancy. 9,10 The summary findings of a recent systematic review pointed to positive associations between poor-quality, unhealthy diets and antenatal depressive and stress symptoms, but the existing evidence base is limited. 11 Within this context, the objective of this study is to evaluate the association of dietary patterns and consumption of specific food groups with mental disorders in pregnant women from southern Brazil.…”
Section: Introductionmentioning
confidence: 99%